EFFICIENCY OF USING "THERAPEUTIC COMBINATION" MASSAGE-NPF TECHNIQUES- KINETIC TECHNIQUES IN RECOVERY OF ACHILLES TENDON RUPTURE - AFTER IMMOBILISATION PHASE - Andreea Potroghiru (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Because this study includes one patient, conclusions of this study is not wish to be generally valid, but are the conclusions drawn from research conducted. The overall conclusion, which can be extracted from studies is as follows: using the "combination therapy" formed by massage techniques, NPF and kinetic techniques immediately after removal of plaster, in rehabilitation treatment of Achilles tendon rupture, has beneficial effects on the evolution of the patient's condition, prognosis for recovery, the efficiency and the recovery period (within the meaning of shortening the latter). Decreases the risk of joint stiffness and contribute to the sustainability of positive results, reduces swelling of stasis that occurs after prolonged immobilization, restores and increases muscle elasticity. Improves local blood flow and venous return in part